Bones and all - Kajganich, David 1969-; DeAngelis, Camille 1980- (Metro-Goldwyn-Mayer Pictures, 2023)
A story of first love between Maren, a young woman learning how to survive on the margins of society, and Lee, an intense and disenfranchised drifter. It's a liberating road odyssey of two young people coming into their own, searching for identity and chasing beauty in a perilous world that cannot abide who they are
Originally released as a motion picture in 2022
Keywords: Liebesfilm; Jugendfilm; Melodrama; Fathers and daughters / Drama; Drifters / Drama; Cannibalism / Drama; Abandoned children / Drama; First loves / Drama; Self-perception in women / Drama; Man-woman relationships / Drama; Self-perception in women; First loves; Drifters; Cannibalism; Abandoned children; Fathers and daughters; Man-woman relationships; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Film adaptations; Fiction films; Feature films; Drama; Horror films; Road films; Romance films; Film; DVD-Video